An economic analysis of women’s employment and divorce - Willi Ascandra; Nasri Bachtiar; Muhammad Nazer (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2019)
Divorce is a condition that might bring economic and social problems. This study examined economic factors that affect probability of divorce on working women in West Sumatera based on Becker’s theory of divorce. Variables tested in this study are income, working hours, number of children, education, sector of work and employment status of ever married working women aged 15 and over, with marital status married and divorce based on National Economy and Sosial Survey 2016. Logistic regression analyses used to obtain likelihood estimate for probability of marital dissolution of employed women. The result of the study revealed that those factors include income, working hours, number of children, education, place of work and employment status, significantly affect the probability of divorce. Education has the maximum likelihood among other factors. The working women with low education have highest risk of divorce followed by those who work more than 40 hours per week, low income (poor), having no children or children less than 2, work in non agriculture and employment status as an employee.